2021
DOI: 10.1021/acssensors.1c00864
|View full text |Cite
|
Sign up to set email alerts
|

Pump-Free Microfluidic Device for the Electrochemical Detection of α1-Acid Glycoprotein

Abstract: α1-Acid glycoprotein (AGP) is a glycoprotein present in serum, which is associated with the modulation of the immune system in response to stress or injuries, and a biomarker for inflammatory diseases and cancers. Here, we propose a pump-free microfluidic device for the electrochemical determination of AGP. The microfluidic device utilizes capillary-driven flow and a passive mixing system to label the AGP with the Os (VI) complex (an electrochemical tag) inside the main channel, before delivering the products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…To date, numerous methods have been proposed for glycoprotein detection. , Relative to dynamic light scattering (DLS), fluorescence, , surface-enhanced Raman scattering (SERS), colorimetry, mass spectrometry (MS), surface plasmon resonance (SPR), electrochemiluminescence (ECL), and photoelectrochemistry (PEC), electrochemical biosensors have received much more attention due to their simplicity, cost-effectiveness, portability, and high sensitivity and selectivity. For the specific capture of target glycoproteins, molecularly imprinted polymers (MIPs), antibodies, , and nucleic acid aptamers are typically used as recognition elements. Among them, nucleic acid aptamers have attracted great interest because they can be chemically synthesized and hold the merits of easy modification, high selectivity and affinity, low cost, and high stability. , For example, Zhao et al reported an electrochemical aptasensor for the signal-on detection of carbohydrate antigen 15-3 (CA15-3) and vascular endothelial growth factor 165 (VEGF 165 ), and the detection limit was 66 ng/mL for CA15-3.…”
mentioning
confidence: 99%
“…To date, numerous methods have been proposed for glycoprotein detection. , Relative to dynamic light scattering (DLS), fluorescence, , surface-enhanced Raman scattering (SERS), colorimetry, mass spectrometry (MS), surface plasmon resonance (SPR), electrochemiluminescence (ECL), and photoelectrochemistry (PEC), electrochemical biosensors have received much more attention due to their simplicity, cost-effectiveness, portability, and high sensitivity and selectivity. For the specific capture of target glycoproteins, molecularly imprinted polymers (MIPs), antibodies, , and nucleic acid aptamers are typically used as recognition elements. Among them, nucleic acid aptamers have attracted great interest because they can be chemically synthesized and hold the merits of easy modification, high selectivity and affinity, low cost, and high stability. , For example, Zhao et al reported an electrochemical aptasensor for the signal-on detection of carbohydrate antigen 15-3 (CA15-3) and vascular endothelial growth factor 165 (VEGF 165 ), and the detection limit was 66 ng/mL for CA15-3.…”
mentioning
confidence: 99%
“…Push-Activated Microfluidic Sensor Systems. Paperbased analytical systems have the advantage of being inherently self-metering and can autonomously fill by capillary action, 55 and paper has previously been paired with microfluidic channels patterned in laminated plastic assemblies 56 to create composite devices with enhanced flow rates. 57 To investigate whether similar fluidic features could be added to these wearable light sensors to aid the user experience and potentially extend the sensor shelf life, we expanded on our initial sensor design to create a push-activated microfluidic network to deliver the activating cystine solution to the capillary volume of the sensor before use (Figure 5A).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In the following study, the authors presented a pump-free microfluidic device with capillary-driven flow and passive mixing system for the electrochemical determination of AGP (α1-Acid glycoprotein) [ 89 ]. The device was composed of four inlets, four microchannels that merge into a single channel, and one outlet.…”
Section: Passive (Non-mechanical Systems)mentioning
confidence: 99%